Sorption and reduction of chromate(VI) ions on Purolite A 830. Issue 15 (1st November 2016) - Wójcik, Grzegorz; Hubicki, Zbigniew
ABSTRACT: Sorption of chromium(VI) and its reduction were investigated in the batch process on Purolite A 830. The kinetic parameters for Cr(VI) and Cr(III) were calculated on the basis of static results. The parameters of Cr(VI) sorption process on the ion exchanger were calculated based on the Freundlich, Langmuir and Temkin isotherms. Sorption of Cr(VI) was studied in the pH range from 1.5 to 10. It was stated that the sorption of Cr(VI) ions depends on solution acidity. The speciation of chromium was investigated in the studied pH range. Reduction of Cr(VI) to Cr(III) under acidic conditions was observed.